The effect of hereditary thrombophilia on recurrent pregnancy loss: a retrospective cohort study - Hasan Berkan Sayal; Mehmet Sinan Beksac (BMC, 2024)
Abstract Objective Thrombophilia screening has been performed in patients with conditions such as previous fetal death, (fetal growth restriction) FGR, preeclampsia, (hemolysis. elevated liver enzyme, low platelet count) HELLP Syndrome, previous abruptio placentae, previous thrombosis in pregnancy, and abnormal placental histology. The actual role of hereditary thrombophilia in recurrent pregnancy loss (RPL) is still debated. This study was intended to determine the incidence of specific gene defects for hereditary thrombophilia and to ascertain their impact on RPL in central Anatolia in Turkey. Methods This retrospective cohort study was performed between January 2012 and December 2022. All pregnant women with a complete hereditary screening profile were included. The investigated gene polymorphisms were methylenetetrahydrofolate reductase (MTHFR) C677T, MTHFR A1298C, Factor V Leiden G1691A, and Factor II prothrombin G20210A. Cases of pregnant women at least two or more consecutive pregnancy losses before 22 weeks of gestation were defined as RPL. The rates of genetic screening and their association with RPL were analyzed. Results RPL was identified in 224 (27.58%) of the 812 pregnant women with complete genetic screening. Although there was no difference in terms of age, body mass index, numbers of ectopic pregnancies, molar pregnancies, or dilatation & curettage (p > 0.05), gravity (2.0 [2.0-3.0] vs. 4.0 [3.0-5.0]), parity (1.0 [1.0-2.0] vs. 1.0 [0-1.0]), live birth (1.0 [1.0-2.0] vs. 1.0 [0-1.0]), anembryonic pregnancy (0 [0-0] vs. 0 [0-0]), miscarriage (0 [0-1.0] vs. 3.0 [2.0-3.0]), and stillbirth (0 [0-0] vs. 0 [0-0]) numbers differed significantly between the groups (p < 0.05). While no significant differences were determined in MTHFR A1298C, Factor V Leiden, factor II prothrombin G20210A, or homocysteine levels (p > 0.05), the homozygous MTHFR C677T positivity rates differed significantly (6.3% in the non-RPL group vs. 11.6% in the RPL group, p = 0.027) . Conclusion The homozygous MTHFR C677T polymorphisms was found to be more frequent in women with RPL. Further studies with larger cohorts are needed to confirm our results.